1985
DOI: 10.1111/j.1365-2222.1985.tb02261.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated late asthmatic reaction due to nickel sulphate without antibodies to nickel

Abstract: Summary A worker with occupational exposure to nickel developed asthma a few months after starting work. Skin prick tests to nickel sulphate were negative. Inhalation challenge with nickel sulphate, at a concentration of 10 mg/ml for 30 min induced a late asthmatic reaction, starting 3 hr after the end of exposure leading to severe nocturnal attack. Tests for antibodies with nickel reactivity were negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…Case reports [18][19][20][21] of occupational asthma due to nickel exposure have been published since McConnell et al [24] first described an asthmatic patient in a metal plating plant. Malo et al [18 21] reported two cases of positive bronchial provocation tests following inhalation of NiSO4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Case reports [18][19][20][21] of occupational asthma due to nickel exposure have been published since McConnell et al [24] first described an asthmatic patient in a metal plating plant. Malo et al [18 21] reported two cases of positive bronchial provocation tests following inhalation of NiSO4.…”
Section: Discussionmentioning
confidence: 99%
“…developed a positive reaction to Ni-HSA. while the other did not [18][19][20][21]. Further evidence for the binding nature of this serum came from elaborate studies done by the same researchers, in which the patient's serum was shown to selectively bind to *' -' Ni [20.21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spirometry was repeated at one and five minutes after exposure. If the fall in FEVI was less than 15% from the baseline, the subject was asked to continue welding for another 15 minutes. The test was discontinued if the subject complained of any respiratory discomfort.…”
Section: Welding Challenge Testmentioning
confidence: 99%